World Customs Organization's Role During the COVID-19-Pandemic: Declarations, Information Distribution, Guidance and Leadership - Carsten Weerth (Public Administration and Customs Administration, 2020)
The worldwide spread of the SARS-CoV-2 virus from Wuhan, Hubei province, China, in 190 countries (according to WHO figures: 219 countries, territories and economic areas) represents an unprecedented threat to Global Health and Global Trade in the times of Globalization – a truly global pandemic spread. The virus triggers COVID-19 (Coronavirus disease 2019), which can range from a symptom-free course to severe respiratory syndrome (pneumonia) and affect the heart, brain and other organ systems as well (a so called multi-organ virus or micro-vascular virus). More than 46.1 million persons were infected worldwide at the beginning of November 2020, more than 1,197,000 persons died from COVID-19 (as of 1 November 2020). The World Customs Organization (WCO) has played and is still playing a crucial part during the COVID-19-pandemic in terms of making (joint declarations), distributing information on the customs procedures and the importance of trade facilitation in a global economic, human and public health emergency and providing guidance together with its partnering International Organizations such as the United Nations (UN), the World Health Organization (WHO), World Trade Organization (WTO) and its stakeholders (such as the ICC, IMO, IRU, UNTAD). All have in the light of the global COVID-19 pandemic joined forces and developed joined trade policies and legal online databases that are accessible freely in the internet in order to help mitigate the social and economic impact COVID-19 on the societies and World Trade and the joined declarations and the joining of forces has mostly been facilitated by the WCO. While many countries issued trade restrictions the International Organizations and business stakeholders called for free trade and trade facilitation. This paper gives an overview of all initiatives, declarations, information and guidance and all newly emerging lists, data collections and free online databases for the global interested public and businesses. All of these items are of the utmost importance to give insight, guidance and help for states, stakeholders and businesses in a global human, public health and economic emergency. Most have been published online on the WCO internet site but some are jointly collected in newly emerging cooperation databases. These databases are constructed to give information seekers overviews about guidance and technical advice for open borders and the facilitation of cross-border trade to ensure open supply chains and the delivery of necessary goods even if borders stay mostly closed for the travel of persons. But the information and databases are also on trade restrictions due to COVID-19. Trade facilitation is the key issue in a global pandemic and the blueprints circulated for more than ten years now are adapted for the COVID-19 pandemic in 2020. Key words: customs law, international organizations, tariff classification, harmonized system (HS) nomenclature, trade facilitation, trade restrictions, Revised Kyoto Convention, international customs law, capacity building.
Keywords: K33; K34; F53; 330; Customs Law; International Customs Law; Trade Facilitation; SARS-CoV-2; World Trade; Global Health